Primary Gastric Squamous Cell Carcinoma with Concurrent H. Pylori Infection and Colonic Metastasis - Jay, Bryanna (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.